2023
DOI: 10.3390/pathogens12010119
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Role of Two-Component Regulatory Systems in Models of Urinary Tract Infections

Abstract: Two-component signaling systems (TCSs) are finely regulated mechanisms by which bacteria adapt to environmental conditions by modifying the expression of target genes. In bacterial pathogenesis, TCSs play important roles in modulating adhesion to mucosal surfaces, resistance to antibiotics, and metabolic adaptation. In the context of urinary tract infections (UTI), one of the most common types infections causing significant health problems worldwide, uropathogens use TCSs for adaptation, survival, and establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 251 publications
2
6
0
Order By: Relevance
“…This finding was in line with previous studies that reported varying frequencies of gelatinase production in P. aeruginosa isolates from clinical sources [18,19]. The presence of gelatinase in wound and urine samples, indicating its potential role in tissue damage and urinary tract infections, was supported by previous research that implicated gelatinase in P. aeruginosa pathogenesis [20,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was in line with previous studies that reported varying frequencies of gelatinase production in P. aeruginosa isolates from clinical sources [18,19]. The presence of gelatinase in wound and urine samples, indicating its potential role in tissue damage and urinary tract infections, was supported by previous research that implicated gelatinase in P. aeruginosa pathogenesis [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…When comparing these results with previous studies, it is evident that the inhibitory effects of P. aeruginosa strains can vary among different environmental sources and target pathogens. These data suggest the presence of different antimicrobial mechanisms employed by the strains [ 20 , 21 ]. Further research is needed to understand these mechanisms and their potential applications in combating pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…CzcRS-dependent zinc induction plays a relevant role in P. aeruginosa since urine can release zinc upon contact with siliconized latex urinary catheters favoring carbepenem-resistance mediated by OprD expression [ 199 , 200 ]. These observations are in line with those performed with the TCS of uropathogens during the onset and progression of urinary tract infections [ 201 ].…”
Section: Gram-negative Bacteriasupporting
confidence: 90%
“…Two-component signaling pathways are critical to bacterial pathogenesis and thus remain a highly active area of investigation across a broad array of major human pathogens ( 61 63 ). Herein, we delineate the global binding characteristics of the critical streptococcal response regulator CovR, in both a wild-type emm3 GAS and a CovS phosphatase-inactive strain.…”
Section: Discussionmentioning
confidence: 99%